2023
DOI: 10.21037/qims-22-443
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter quantitative 18F-fluorodeoxyglucose positron emission tomography performance harmonization: use of hottest voxels towards more robust quantification

Abstract: Background: Harmonization methods reduce variability between different make and models of positron emission tomography (PET) scanners. The study aims to explore harmonization strategies that lead to comparable and robust quantitative metrics in a multicenter setting.Methods: NEMA IEC Phantom data acquisition was performed for low and high spheres-to-background ratios (SBR4:1 and 10:1) on six PET/CT (computed tomography) scanners. Different reconstruction sets, including the number of sub-iterations, number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Prior to the study, quality control of the protocol at each site revealed no evidence of bias [ 34 ]. A 3-D acquisition mode was used for all PE/CT images following a 45 to 60-minute uptake period from the skull to the mid-thigh.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the study, quality control of the protocol at each site revealed no evidence of bias [ 34 ]. A 3-D acquisition mode was used for all PE/CT images following a 45 to 60-minute uptake period from the skull to the mid-thigh.…”
Section: Methodsmentioning
confidence: 99%